Correlation Analysis Between the Growth of Wild-Simulated Ginseng and the Soil Bacterial Community in the Central Region of South Korea - Kim, Kiyoon; Yun, Yeong-Bae; Park, Myeongbin; Um, Yurry (Applied sciences, 2025)
Wild-simulated ginseng (WSG, Panax ginseng C.A. Meyer) is the most important medicinal plant naturally cultivated in the forestry environment. The growth and active component content of WSG can be influenced by various environmental factors, such as climate conditions, physiognomy, soil properties, and soil bacterial structure. The aim of this study was to investigate the relationship between the growth characteristics of WSG and the soil bacterial community living in a rhizosphere environment. Experimental subjects were 7- and 13-year-old WSG cultivated in the central region (Yeongju) of Korea. The growth characteristics of WSG, divided into aerial parts, root parts, and weight parts, were measured. Rhizome length was significantly higher for 13-year-old WSG, while the number of rootlets was higher for 7-year-old WSG. As a result of analyzing the soil bacterial communities of WSG cultivation sites using next-generation sequencing (NGS), Proteobacteria and Holophagae were found to be the dominant species in the phylum level and class level, respectively. Rhizome length was positively correlated with Bacteroidetes at the phylum level, but it was negatively correlated with Thermoleophilia and Gemmatimonadetes at the class level. Pedospharae showed a negative correlation with the number of leaflets and petiole length, while Clostridia showed a positive correlation with the number of rootlets. The growth of WSG might vary depending on the environment in which it is cultivated. It is especially affected by soil properties and soil bacterial communities. Therefore, in future studies, it will be necessary to isolate and identify soil microorganisms living in WSG cultivation sites and then confirm their growth-promoting effects on WSG.